2013
DOI: 10.14429/dsj.63.2458
|View full text |Cite
|
Sign up to set email alerts
|

Application of Metallic Strip Gratings for Enhancement of Electromagnetic Performance of A-sandwich Radome

Abstract: Enhancement of the electromagnetic (EM) performance characteristics of A-sandwich radome wall over X-band using metallic strip gratings is presented in this work. Equivalent transmission line method in conjunction with equivalent circuit model (ECM) is used for modeling the A-sandwich radome panel with metallic strip gratings and the computation of radome performance parameters. Metallic strip grating embedded in the mid-plane of the core and those in the skin-core interface are the configurations considered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previously very limited studies are reported on effects of radome on the active array radiation patterns [19][20][21][22][23] . Studies have been carried out to understand the electrical performance of A-sandwich radome by strip loading 24. A thick FSS radome wall has been proposed for airborne application based on mode-matching generalised scattering matrix approach 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously very limited studies are reported on effects of radome on the active array radiation patterns [19][20][21][22][23] . Studies have been carried out to understand the electrical performance of A-sandwich radome by strip loading 24. A thick FSS radome wall has been proposed for airborne application based on mode-matching generalised scattering matrix approach 25 .…”
Section: Introductionmentioning
confidence: 99%